Genome-wide characterization and expression analysis of the CONSTANS-like gene family of Juglans mandshurica Maxim - Wu,Jingwen; Zhang,Mengmeng; Gao,Yue; Li,Shuhan; Jia,Ruoxue; Zhang,Lijie (PeerJ, 2025)
The zinc-finger proteins encoded by the CONSTANS-like (COLs) gene family in Juglans mandshurica Maxim. play a significant role in regulating photoperiod-dependent flowering time, as well as in various processes such as growth and development. In this study, 15 members of the CONSTANS-like gene family were identified based on the genomic data of Juglans mandshurica. All of these proteins possess an N-terminal zinc-finger B-box domain and a C-terminal CCT domain. Phylogenetic analysis indicates that the JmCOLs proteins can be divided into three subgroups, with gene structures and motif compositions varying among these subgroups. Chromosomal analysis reveals that the 15 JmCOLs genes are distributed across nine chromosomes. The promoters of genes in this family contain stress-related cis-acting elements, hormone-related response elements, and other elements associated with growth and development. Notably, the most prominent elements are the light-responsive elements, suggesting that genes in this family are predominantly expressed in leaves. The expression patterns of JmCOLs genes differ among the members. Specifically, JmCOL5 and JmCOL10 are expressed exclusively in flower buds (p < 0.05). Throughout the 10 stages of flower bud development, the overall expression level of JmCOL4a peaks at approximately 50 to 100 times higher than its lowest point. The expression pattern of JmCOL5, which first reaches its maximum during the physiological differentiation stage of protogynous male flower buds before declining, suggests its potential involvement in the development of heteromorphic and dichogamous flowers.
Keywords: Juglans mandshurica Maxim.; CONSTANS-likes; Genome-wide identification; Expression pattern; Photoperiod; Flower development